Targeting GRK2 by gene therapy for heart failure: benefits above β-blockade - Reinkober, Julia; Tscheschner, Henrike; Pleger, Sven Torsten; Most, Patrick; Katus, Hugo; Raake, Philip (Gene therapy, 2012)
Heart failure (HF) is a common pathological end point for several cardiac diseases. Despite reasonable achievements in pharmacological, electrophysiological and surgical treatments, prognosis for chronic HF remains poor. Modern therapies are generally symptom oriented and do not currently address specific intracellular molecular signaling abnormalities. Therefore, new and innovative therapeutic approaches are warranted and, ideally, these could at least complement established therapeutic options if not replace them. Gene therapy has potential to serve in this regard in HF as vectors can be directed toward diseased myocytes and directly target intracellular signaling abnormalities. Within this review, we will dissect the adrenergic system contributing to HF development and progression with special emphasis on G-protein-coupled receptor kinase 2 (GRK2). The levels and activity of GRK2 are increased in HF and we and others have demonstrated that this kinase is a major molecular culprit in HF. We will cover the evidence supporting gene therapy directed against myocardial as well as adrenal GRK2 to improve the function and structure of the failing heart and how these strategies may offer complementary and synergistic effects with the existing HF mainstay therapy of β-adrenergic receptor antagonism.